Co-Microencapsulation of Sacha Inchi (Plukenetia huayllabambana) Oil with Natural Antioxidants Extracts - Chasquibol, Nancy (2023)
Sacha inchi (Plukenetia huayllabambana) oil was co-microencapsulated with natural antioxidant extracts (NAE), such as camu-camu (Myrciaria dubia (HBK) Mc Vaugh) fruit, Añil variety Andean potato (Solanum tuberosum andigenum, and elderberry fruit (Sambucus peruviana). Gum Arabic and the ternary combination of gum Arabic (GA) + maltodextrin (MD) + whey protein isolate (WPI) at different formulations were used as coating materials for the encapsulation process using spray-drying. The moisture content, particle size distribution and morphology, total phenolic content, antioxidant activity, fatty acid and sterol composition, oxidative stability, and shelf-life were evaluated. Co-microcapsules of sacha inchi (P. huayllabambana) oil with camu camu skin extract (CCSE) at 200 ppm encapsulated with GA + MD + WPI had the highest total polyphenol content (4239.80 µg GAE/g powder), antioxidant activity (12,454.00 µg trolox/g powder), omega-3 content (56.03%), β-sitosterol (62.5%), greater oxidative stability (Oxidation Onset temperature of 189 °C), higher shelf-life (3116 h), and smaller particle sizes (6.42 μm). This research enhances the knowledge to obtain microcapsules containing sacha inchi (P. huayllabambana) oil with natural antioxidant extracts that could be used for the development of functional foods. Further research is needed to study the potential interactions and their influence between the bioactive components of the microcapsules and the challenges that may occur during scale-up to industrial production. // Resumen: El aceite de sacha inchi (Plukenetia huayllabambana) fue co-microencapsulado con extractos antioxidantes naturales (NAE), como el fruto del camu-camu (Myrciaria dubia (HBK) Mc Vaugh), la papa andina variedad Añil (Solanum tuberosum andigenum) y el fruto del saúco (Sambucus peruviana Se utilizó goma arábiga y la combinación ternaria de goma arábiga (GA) + maltodextrina (MD) + aislado de proteína de suero (WPI) en diferentes formulaciones como materiales de recubrimiento para el proceso de encapsulación mediante secado por aspersión. El contenido de humedad, distribución del tamaño de partícula y se evaluó morfología, contenido fenólico total, actividad antioxidante, composición de ácidos grasos y esteroles, estabilidad oxidativa y vida útil Co-microcápsulas de aceite de sacha inchi (P. huayllabambana) con extracto de piel de camu camu (CCSE) a 200 ppm encapsuladas con GA + MD + WPI tuvo el mayor contenido de polifenoles totales (4239.80 µg GAE/g polvo), actividad antioxidante (12,454.00 µg trolox/g polvo), contenido de omega-3 (56.03%), β-sitosterol (62.5%), mayor estabilidad oxidativa (temperatura de inicio de oxidación de 189 °C), mayor vida útil (3116 h) y tamaños de partículas más pequeños (6,42 μm). Esta investigación potencia el conocimiento para obtener microcápsulas que contienen aceite de sacha inchi (P. huayllabambana) con extractos antioxidantes naturales que podrían ser utilizadas para la elaboración de alimentos funcionales. Se necesita más investigación para estudiar las posibles interacciones y su influencia entre los componentes bioactivos de las microcápsulas y los desafíos que pueden surgir durante la ampliación a la producción industrial.